2005
DOI: 10.1161/01.cir.0000158435.98035.8d
|View full text |Cite
|
Sign up to set email alerts
|

Plaque Rupture After Short Periods of Fat Feeding in the Apolipoprotein E–Knockout Mouse

Abstract: Background-These studies examined the early time course of plaque development and destabilization in the brachiocephalic artery of the apolipoprotein E-knockout mouse, the effects of pravastatin thereon, and the effects of pravastatin on established unstable plaques. Methods and Results-Male apolipoprotein E-knockout mice were fed a high-fat, cholesterol-enriched diet from the age of 8 weeks. Animals were euthanized at 1-week intervals between 4 and 9 weeks of fat feeding. Acutely ruptured plaques were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
205
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(217 citation statements)
references
References 23 publications
12
205
0
Order By: Relevance
“…Therefore, the result shows that simvastatin promote an accumulation of Tregs within the atherosclerotic plaques. Interestingly, we did not find a significant difference in serum levels of total cholesterol, triglycerides and LDL cholesterol with and without sim- vastatin in ApoE -/-mice, which was consistent with the previous studies (27,28), indicating that simvastatin influenced the number of Tregs in plaques, independent of its lipid-lowering properties. Tregs secrete two major cytokines (TGF-β and IL-10), which are associated with their survival and function (30).…”
Section: Tregs Are a Unique Subset Of T Cells Although The Number Ofsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the result shows that simvastatin promote an accumulation of Tregs within the atherosclerotic plaques. Interestingly, we did not find a significant difference in serum levels of total cholesterol, triglycerides and LDL cholesterol with and without sim- vastatin in ApoE -/-mice, which was consistent with the previous studies (27,28), indicating that simvastatin influenced the number of Tregs in plaques, independent of its lipid-lowering properties. Tregs secrete two major cytokines (TGF-β and IL-10), which are associated with their survival and function (30).…”
Section: Tregs Are a Unique Subset Of T Cells Although The Number Ofsupporting
confidence: 93%
“…However, no study has investigated the effect of statins on Tregs in atherosclerotic plaques. As well known, atherosclerotic lesions can develop in ApoE -/-mice throughout the arterial tree and such mice are thought to be a wellestablished genetic animal model of atherosclerosis, with many morphologic characteristics resembling that in humans (28). Therefore, in this study, we induced atherosclerotic plaque in ApoE -/-mice by placing a silastic perivascular collar around the right common carotid artery and introducing a lipid-rich diet (20,21).…”
Section: Tregs Are a Unique Subset Of T Cells Although The Number Ofmentioning
confidence: 99%
“…We used ApoE-/-mice, a type of spontaneous atherosclerosis animal model, which develop atherosclerotic lesions slowly in its aortic tissues throughout the whole arterial tree. Several publications have been issued recently which demonstrated the vulnerability of plaques in apoE-/-mice, especially in the high-fat feeding apoE-/-mice [26][27][28][29]. Intramural bleeding was also reportedly observed in the brachiocephalic arteries at an older age (60 weeks old) possibly caused by plaque rupture [43].…”
Section: Discussionmentioning
confidence: 98%
“…Recently, some investigators have also observed spontaneous plaque rupture in the brachiocephalic arteries and subsequent sudden death in aged ApoE-/-mice [26][27][28][29]. These data suggest that ApoE-/-mice could be a useful model for the evaluation of tracers for detecting unstable atherosclerotic lesions.…”
Section: Introductionmentioning
confidence: 87%
“…Compared to rodents, human plaques show more complex lesions and specifically more calcification. Experimental characterization of plaque instability is challenging as mouse models for atherosclerotic plaque rupture are scarcely available [44][45][46] and not well characterized [47].…”
Section: Discussionmentioning
confidence: 99%